Low-Income Developing Countries and G-20 Trade and Investment Policy - World Bank Group (World Bank, Washington, DC, 2015)
This background paper provides information on the study of the Group of 20 (G-20) and challenges faced by low-income developing countries (LIDCs). The study analyzes LIDCs development challenges and how G-20 economic policies can be coordinated so they can contribute to creating an enabling environment for their development. The focus of the paper is the role that trade and investment policies of G-20 countries play in this context. The paper is composed of three parts 1) the characteristics of LIDCs integration in the world economy, 2) the evolution of G-20 policies that affect LIDCs integration, and 3) the potential for changes in the G-20 trade and investment policy landscape to benefit LIDCs.